Data for: Extinction drives both expansion and contraction of morphological disparity in Trilobites - Balseiro, Diego (2025)
Data files and R scripts for main and supplementary analysis. See README.txt for further details. Datos y scripts de R para los análisis principales y suplementarios. Ver README.txt para más detalles.